Soil arching and load transfer mechanism for slope stabilized with piles - Kahyaoglu, Mehmet Rifat; Onal, Okan; Imançlı, Gökhan; Ozden, Gürkan; Kayalar, Arif S. (Journal of Civil Engineering and Management, 2012)
In this study, the effects of pile spacing and pile head fixity on the moment and lateral soil pressure distribution along slope stabilizing piles are investigated. A slice from an infinitely long row of piles with fixed pile tip in an inclined sand bed was simulated with an experimental test setup. Surficial soil displacements were monitored and relative displacements between soil particles were determined by recording time-lapse images during the test in order to observe the soil arching mechanism on the soil surface. The load transfer process from moving soil to piles and behavior of soil around piles were observed and evaluated by the different test setups. It was observed that decrease in pile spacing causes an increase of load carried per pile. This behavior, which was significantly influenced by the pile head boundary conditions, can only be explained by soil arching that existed between the piles along their lengths.